Dampak Otonomi Daerah Terhadap Kapasitas Fiskal Kabupaten Timor Tengah Utara Provinsi NTT - Kamilaus Konstanse Oki (Ekopem: Jurnal Ekonomi Pembangunan, 2019)
Regional autonomy is an independence right given by the central government to the regions to take care of the interests of the community. The impact of regional autonomy is to create fiscal capacity independence as the basic capital of regional development. The fiscal capacity of In the District of North Central Timor originates from Regional Original Income, balancing funds, and other legitimate regional income. The problem in this study is to find out how much the impact of regional autonomy on the fiscal capacity of in the District of North Central Timor. This study aims to measure fiscal capacity capabilities. The study was conducted in the District of North Central Timor using a quantitative descriptive approach. The results of the analysis show that the average level of regional independence in the relationship pattern is in the instructive category, meaning that regional financial capacity is very low in financing the implementation of regional development. Factors in financial inability of the in the District of North Central Timor because the local government is less creative in utilizing local resources properly, also because the contribution of revenue sources is still minimal.